Pertanggungjawaban Pidana Pengendara atas Pemalsuan Surat Samsat dalam Perspektif Hukum Pidana Indonesia - Lindriyani Hamzah; Roy Marthen Moonti (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the criminal liability of motorists for falsifying Samsat (Vehicle Registration Certificate) documents from the perspective of Indonesian criminal law. The background of this study is based on the importance of Samsat documents, such as the Vehicle Registration Certificate (STNK), Vehicle Registration Certificate (TNKB), and proof of vehicle tax approval, as proof of motor vehicle legality. Falsification of these documents not only raises administrative issues but also has the potential to constitute a criminal act of document forgery, disrupting legal certainty, administrative order, and public trust in official state documents. This study aims to analyze the forms of criminal liability of motorists and examine gaps in law enforcement regarding Samsat document forgery. The type of research used is normative legal research with statutory, conceptual, and case-based approaches. The results indicate that motorists can be held criminally liable if they are proven to know or reasonably suspect that the Samsat document they are using is counterfeit, but continue to use it to gain profit, avoid inspection, or legalize problematic vehicles. This liability can take the form of using the counterfeit document, creating the counterfeit document, participating in the crime, or committing a continuing act. However, law enforcement still faces challenges in proving fault, weak digital verification, and suboptimal disclosure of forgery networks. Therefore, proportional, evidence-based law enforcement supported by the integration of the Samsat (State Vehicle Registration Agency) system is necessary.